Perceptions, Expectations, and Entrepreneurship: The Role of Extreme Events - Tilman Brück; Fernanda Llussá; José Tavares (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We provide, for the first time, comparative evidence of the impact of various types of extreme events - natural disasters, terrorism, and violent conflicts - on the perceptions of entrepreneurs concerning some key entrepreneurial issues - such as fear of failure in starting a business venture, whether individuals expect that good opportunities are likely to emerge in the next six months, and the expected level of competition stemming from creating new ventures. The occurrence of extreme events is likely to be exogenous to the perceptions affecting it so that we can identify a causal link from events to entrepreneurs and their perceptions. Using individual-level data from 43 countries from the period 2002 to 2005, we find that neither indicator of the intensity of extreme events has a significant impact on entrepreneurial activity, when country characteristics are not controlled for. Once invariant country characteristics are taken into account, we find that Terrorist Attacks have a positive and significant impact on business creation, Natural Disasters have a positive and negative impact on entrepreneurial activity, and Violent Conflict has no significant effect. These results are consistent with differential impacts of extreme events on perception variables such as Fear of Failure, Expected Business Opportunities, and Expected Level of Competition. Our results suggest that extreme events, while costly at the aggregate level, may induce a positive response in terms of entrepreneurial activity in specific circumstances. There is hence scope for entrepreneurs, and policies supporting them, to create growth from the ruins of extreme events.
Keywords: 330